The interplay between public procurement of innovation and R&D grants: Empirical evidence from Belgium - Dirk Czarnitzki; Malte Prüfer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This paper investigates the impact of Public Procurement of Innovation (PPI) and Research and Development (R&D) grants on firms' R&D investment using data from Belgian R&D-active firms over the past decade. Our empirical analysis robustly reveals a non-negligible crowding-out effect between the two instruments, suggesting a substitutive relationship. While each policy individually positively influences R&D investment, their combined implementation diminishes their effectiveness. These results challenge prevailing evidence and emphasize the need for a careful policy implementation, raising policymakers' awareness against a blanket increase in innovation policies without considering potential interactions.
Keywords: H57; O38; 330; Public procurement of innovation; Research and Development; Econometric policy evaluation; Crowding-out